Space Frame Buckling - Buchert, Kenneth P. (Engineering Journal, 1968)
The large dome structure is being used more and more because of its structural efficiency, its low cost, and its beauty. The Houston Astrodome (see Fig. 1) is an illustration of future trends in large covered areas. Domes have been built using structural shapes, tubing, shells with stiffeners and composite materials. Buckling analysis is one of the most important considerations facing the designer of such a structure. If buckling failure occurs, it is often sudden and often results in complete collapse of the structure. The failure of the 300-ft diameter dome in Bucharest, Rumania1, is but one example of such a collapse. The purpose of this report is to show that the designer can calculate the general buckling load in the nonlinear stress-strain range and can take into account the important factors in buckling such as yield strength, edge conditions, construction and fabrication tolerances, and residual stresses in structural members.